CTPA, DECT, MRI, V/Q Scan, and SPECT/CT V/Q for the noninvasive diagnosis of chronic thromboembolic pulmonary hypertension: A protocol for systemic review and network meta-analysis of diagnostic test accuracy. Issue 34 (August 2019) - Xu, Shuanglan; Yang, Jiao; Zhu, Yun; Xu, Shuangyan; Liu, Jie; Deng, Yishu; Wei, Li; Yang, Mei; Huang, Xiaoxian; Cao, Bing; Zhang, Chunfang; Zhao, Fangyun; et al.
Abstract: Background: To determine the diagnostic accuracy of techniques with chronic thromboembolic pulmonary hypertension (CTEPH) patients via a protocol for systemic review and network meta-analysis. Methods: We will search PubMed, EMBASE, Web of Science, and Google Scholar from inception to October 1, 2018. The reference lists of the retrieved articles are also consulted. Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) will be used to assess the risk of bias in each study. The direct meta-analyses, network meta-analyses, and ranking of competing diagnostic tests will be used by STATA 12.0 and WINBUGS 1.4. Heterogeneity and inconsistency are assessed. Results: This study is ongoing, will be submitted to a peer-reviewed journal publication once completed. Conclusion: This study will provide a comprehensive evidence summary of diagnostic test accuracy in detecting the CTEPH, and can help patients and clinicians to select appropriate or best diagnostic test. Ethics and Communication: No ethical approval and patient consent are required, because it is based on published researches. PROSPERO registration number: CRD42019121279.